2014
DOI: 10.3732/apps.1400064
|View full text |Cite
|
Sign up to set email alerts
|

Genome and metagenome sequencing: Using the human methyl‐binding domain to partition genomic DNA derived from plant tissues

Abstract: • Premise of the study: Variation in the distribution of methylated CpG (methyl-CpG) in genomic DNA (gDNA) across the tree of life is biologically interesting and useful in genomic studies. We illustrate the use of human methyl-CpG-binding domain (MBD2) to fractionate angiosperm DNA into eukaryotic nuclear (methyl-CpG-rich) vs. organellar and prokaryotic (methyl-CpG-poor) elements for genomic and metagenomic sequencing projects.• Methods: MBD2 has been used to enrich prokaryotic DNA in animal systems. Using gD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The novel method based on methylation-based enrichment increased the concentration of plastid DNA by 30% which is in the range found by a previous pilot study [ 84 ]. It is a suitable method for enriching the organellar genome before sequencing.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The novel method based on methylation-based enrichment increased the concentration of plastid DNA by 30% which is in the range found by a previous pilot study [ 84 ]. It is a suitable method for enriching the organellar genome before sequencing.…”
Section: Discussionsupporting
confidence: 64%
“…enriched for plastid) and a methylation-rich fraction (e.g. depleted in plastid) [ 84 ]. This method has the advantage that it uses a small quantity of dry material (below 40 mg) and is suitable for non-model organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Yigit et al . () showed that gDNA could be partitioned into a high‐methylated‐CpG nuclear fraction, and a fraction of low‐methylated‐CpG elements. The methyl‐poor fraction was enriched for plastids by 3.2‐ to 11.2‐fold, depending on the species in question.…”
Section: Library Preparation Strategiesmentioning
confidence: 99%
“…For example, Feehery et al ( 111 ) used magnetic beads with methyl-binding domains that specifically bind to a portion of mammalian and fish DNA to reduce the presence of these nontarget molecules (also see reference 112 ) (commercially available kits include the NEBNext microbiome DNA enrichment kit). Yigit et al ( 113 ) extended this approach to plant tissues and selectively shifted the ratio of nuclear to organellar DNA obtained from five model angiosperm taxa (also see reference 114 ).…”
Section: Resultsmentioning
confidence: 99%